UTILIZATION OF COAL ASH MATERIAL FOR SUBBASE COURSE WITH HIGH ABRASION AGGREGATE - Cassiophea, Lola (BALANGA: Jurnal Pendidikan Teknologi dan Kejuruan, 2014)
This study attempted to use coal ash as a substitute material that meets the criteria for subbase mixtures. Initial mixture consisting of soil, sand and gravel. The mixture was separated into three variations in the ratio of each of the Variation I (10:50:40), Variation II (10:45:45) and the Variation III (10:60:30). Comparison of variation with the lowest CBR value is used as a benchmark for subbase mixed with coal ash that is Variation I. Subbase mixture was then divided into two compositions of coal ash as a substitute material for sand and as a substitute material for gravel. Composition I as a substitute consisting of sand, gravel and coal ash (fly ash, bottom ash) are distinguished into three variations in the ratio of each of the Variations IA (10:50: (10:30)), IB (10: 50: (15:25)), IC (10:50: (20:20)). Composition II as a substitute for gravel composed of soil, coal ash brick, brick fine coal ash, which is also divided into three variations of the IIA, IIB, IIC with the same ratio of each composition 10:50:40, the difference is the content of coal ash in coal ash brick respectively 10% fly ash, 20% fly ash and 25% bottom ash. Test on subbase layer consisting of a sieve analysis test, atterberg limit, compaction, CBR, and dissolved heavy metals test. The results showed non-soaked CBR value for all variations subbase mixed with coal ash which has been meeting the specifications required for subbase, while the condition of soaked CBR II only variations that meet specifications. Variation IIA is a good subbase mixture to use.